Development of a Model for Enhancing Health Literacy in Preventing Coronavirus Disease Infections Among 4th-6th Grade Students in Chumphonburi District, Surin Province - Thangthum, Natnaree; Deeying, Jaded (Journal of the office of disease prevention and control 9 Nakhon Ratchasima, 2023)
This action research aimed to enhance the health literacy model for preventing coronavirus disease 2019 (COVID-19) among 4th–6th grade students in Chumphonburi District, Surin Province. The research process consisted of three phases: 1) examination of health literacy and behaviors to prevent COVID-19: The participants included 328 students in grades 4th–6th. 2) model development and Trial: The PAOR Model (Planning, Action, Observation, and Reflection) was applied. A total of 40 participants were selected using purposive sampling. 3) evaluation of the development Model and satisfaction: This involved focus group discussions, observations, and interviews. Descriptive statistics were used for quantitative data analysis, and paired t-tests were conducted for the compared mean. Content analysis was applied for qualitative data. The results indicated that the model for enhancing health literacy to prevent coronavirus disease 2019 in schools consisted of the following components: (1) personnel development: Equipping individuals with performance readiness, (2) integrated performance: Establishing a school working group for health literacy, (3) knowledge and skills development: Providing facilitators with necessary knowledge and skills, (4) area selection: Identifying specific areas for focus, and (5) monitoring and evaluation: Conducting a 9-week trial health literacy promotion program with a sample of forty participants. After implementing the trial program, the students showed statistically significant improvement, with higher mean scores for health literacy and COVID-19 preventive behaviors (p-value < 0.001). Additionally, satisfaction with the health literacy promotion was at the highest level. The model development for health literacy promotion and behavior to prevent COVID-19 infections was found to be effective, feasible to practice, and consistent with the area's problems.